Persepsi Mahasiswa pada Pembelajaran Daring melalui Pemanfaatan Google Classroom dan Google Meet di UIN Maulana Malik Ibrahim Malang - Kivah Aha Putra; Ratna Nulinnaja; Misbahul Munir (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2020)
Apart from Coronavirus Disease 2019, Indonesia is now also affected by the mutation of the corona virus B.1.1.7. This means that Indonesia will still struggle to overcome this condition so that it can be stable in all fields. Education, one of which is at the tertiary level, must continue to run stably. To strengthen learning is carried out remotely by utilizing platforms, one of which is using Google Classroom and Google Meet in learning Islamic Cultural History (SPI) to prevent transmission of the Covid 19 virus. This study uses a qualitative method. Through a survey via Google Form which is distributed to students majoring in Physics who are active in the 2020/2021 teaching. The result is that 90.1% of students are motivated to attend lectures because they do not require a lot of quotas, and the features used on the platform are very easy to operate and very attractive.